Răspuns :
[tex] {x}^{2} - 144 = {x}^{2} - {12}^{2} = (x - 12) \times (x + 12)[/tex]
[tex] {x}^{2} - 49 = {x}^{2} - {7}^{2} = (x - 7) \times (x + 7)[/tex]
[tex] {a}^{2} - 36 = {a}^{2} - {6}^{2} = (a - 6) \times (a + 6)[/tex]
[tex] {t}^{2} - 36 = {t}^{2} - {6}^{2} = (t - 6) \times (t + 6)[/tex]
Răspuns:
Explicație pas cu pas:
x²- 144 = x²- 12² = (x + 12) · (x - 12)
x²- 49 = x²- 7² = (x + 7) · (x - 7)
a² - 36 = a²- 6² = (a + 6) · (a - 6)
t² - 36 = t²- 6² = (t + 6) · (t - 6)
✳ Am folosit formula:
(a + b) · (a - b) = a² - b²
sau
a² - b² = (a + b) · (a - b)